2012
DOI: 10.3389/fphys.2012.00451
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous kinetics of AKT signaling in individual cells are accounted for by variable protein concentration

Abstract: In most solid cancers, cells harboring oncogenic mutations represent only a sub-fraction of the entire population. Within this sub-fraction the expression level of mutated proteins can vary significantly due to cellular variability limiting the efficiency of targeted therapy. To address the causes of the heterogeneity, we performed a systematic analysis of one of the most frequently mutated pathways in cancer cells, the phosphatidylinositol 3 kinase (PI3K) signaling pathway. Among others PI3K signaling is acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Therefore, a mammalian cell has a huge number of molecules even if the same concentrations of proteins are present in yeast and bacterial cells. For example, the EGF signaling pathway consists of 10 3 –10 7 molecules [40] and the HGF signaling pathway consists of 10 4 –10 7 molecules [9]. On the other hand, E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a mammalian cell has a huge number of molecules even if the same concentrations of proteins are present in yeast and bacterial cells. For example, the EGF signaling pathway consists of 10 3 –10 7 molecules [40] and the HGF signaling pathway consists of 10 4 –10 7 molecules [9]. On the other hand, E .…”
Section: Discussionmentioning
confidence: 99%
“…In other signaling pathways, ranges of measured CV of signaling proteins were 8%– 75% in the hepatocyte growth factor (HGF) signaling pathway [9], 21%– 28% in the apoptotic intrinsic pathway [8], and 15%– 30% in normally cycling human cells [42]. Thus, estimated CV was included in the range of observed protein variability, indicating that our method is useful for estimating or predicting the variability of all signaling proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been shown that in single cells pERK levels do not vary continuously, but instead they manifest bistable fluctuations between minimal and maximal pERK, with higher levels of stimulus causing an increase in the frequency and duration of these spikes of ERK activation (37,69). The same does not appear to be the case for Akt, however; it has been shown that pAkt levels in individual cells are distributed stochastically around the mean (72). Nevertheless, because of the limitations arising from averaging over many cells, we focus here on identifying quantitative, empirical relationships between key factors and events, rather than proposing detailed mechanistic or network models.…”
Section: Discussionmentioning
confidence: 84%
“…In the liver, hepatocyte growth factor (HGF)-induced activation of the phosphatidylinositol 3 kinase (PI3K) signaling pathway contributes to hepatocyte proliferation and consequently to liver regeneration in response to damage. A comparison of PI3K pathway activation upon HGF stimulation at the cell population and single cell level was performed in primary mouse hepatocytes and in the hepatoma cell line Hepa1-6 (Meyer et al, 2012). At the cell population level, the activation kinetics of the PI3K pathway were analyzed by combining experimental data with a deterministic coupled ODE based model.…”
Section: Growth Factor Induced Signaling Pathways and Cell Cycle Progmentioning
confidence: 99%